2019
DOI: 10.18632/aging.102324
|View full text |Cite
|
Sign up to set email alerts
|

Mogroside V protects porcine oocytes from in vitro ageing by reducing oxidative stress through SIRT1 upregulation

Abstract: Postovulatory ageing compromises oocyte quality and subsequent development in various manners. We aimed to assay the protective effects of mogroside V on porcine oocyte quality during in vitro ageing and explore the related causes. We observed that mogroside V can effectively maintain normal oocyte morphology and early embryo development competence after prolonged culture for 24 h. Moreover, mogroside V can markedly reduce reactive oxygen species (ROS) levels, alleviate spindle formation and chromosome alignme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 40 publications
3
25
0
1
Order By: Relevance
“…Then, we applied the porcine oocyte as a study model and found that MV treatment evidently alleviated the LPS-induced meiotic defects. Similarly, we previously revealed that MV has protective and promotive effects on porcine oocyte maturation and competence ( Nie et al, 2019 , 2020 ). Thus, our findings suggest that MV is a candidate agent for amelioration of LPS-induced oocyte meiotic defects.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Then, we applied the porcine oocyte as a study model and found that MV treatment evidently alleviated the LPS-induced meiotic defects. Similarly, we previously revealed that MV has protective and promotive effects on porcine oocyte maturation and competence ( Nie et al, 2019 , 2020 ). Thus, our findings suggest that MV is a candidate agent for amelioration of LPS-induced oocyte meiotic defects.…”
Section: Discussionsupporting
confidence: 55%
“…As a potent antioxidant, MV has significant oxygen free radical scavenging capacity and attenuates lipid peroxidation induced by Fe 2+ or H 2 O 2 ( Li et al, 2014 ). In addition, our previous studies demonstrated that MV reduces reactive oxygen species (ROS) levels and promotes mitochondrial function to improve porcine oocyte IVM ( Nie et al, 2020 ) and protects oocyte quality from deterioration during in vitro aging ( Nie et al, 2019 ). Furthermore, protective effects of MV against LPS-induced diseases, such as alleviation of LPS-induced memory impairment and acute lung injury in mice and prevention of LPS-induced oxidative stress injury in RAW264.7 cells have been reported ( Di et al, 2011 ; Shi et al, 2014 ; Li et al, 2019 ; Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Still oocyte aging in vitro results in the abnormal distribution and function disorder of cytoplasmic organelles. For example, the most widely studied organelle is mitochondria, with confirmed dysfunction in aged oocytes such as low membrane potential, reduced ATP content and mutated mitochondrial DNA 57 , 58 . The aged porcine oocytes has been reported to exhibit disordered ER clusters and impaired ER calcium homeostasis 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MV reduced intracellular ROS and increased the mRNA expression of oxidative stress-related genes (SOD, CAT, and SIRT1) while enhancing mitochondrial function ( Nie et al, 2020 ). MV markedly reduces the decline in porcine oocyte quality during in vitro aging, possibly by reducing oxidative stress and early apoptosis in aged oocytes while improving mitochondrial contents and function ( Nie et al, 2019 ).…”
Section: Natural Antioxidant-based Interventions To Reduce Oxidative mentioning
confidence: 99%